The Use of Sentence Structure Technique (SKOP) and Its Implications on Malay Language Writing among Level 2 Pupils: A Teacher Perception Analysis - Ng , Ching Yee (Journal of Research, Innovation, and Strategies for Education (RISE), 2024)
This study examines the effectiveness of the Sentence Structure Technique (SKOP) in teaching Malay language writing for Level 2 students at a primary school in Johor Bahru, Malaysia. Writing is an essential skill, yet students still face challenges in mastering grammar and accurate writing. Therefore, this study aims to evaluate teachers' perceptions of the SKOP technique and its effectiveness in improving students' writing skills. A quantitative approach was employed using a 5-point Likert scale questionnaire and pre- and post-tests to assess students' writing skills. The sample consisted of 7 teachers and 338 Level 2 students, with a three-month intervention of the SKOP technique. Analysis of the mean and median revealed that most items in the questionnaire consistently scored around 4 (Agree), indicating teachers' positive perceptions of this technique. The findings also demonstrated significant improvement in the writing performance of Year 4, 5, and 6 students, with increases of 68.57% for Year 4, 24.60% for Year 5, and 13.85% for Year 6. These empirical data provide evidence that the SKOP technique effectively helps students structure and understand sentences, thereby enhancing their writing proficiency. This study recommends that the SKOP technique be continued and expanded within the Malay language curriculum and highlights important implications for educators and policymakers in improving students' writing skills in Malaysia.
Keywords: Sentence Structure Technique; Malay Language; Intervention; Writing; Effectiveness.